Internally generated conscious contents: interactions between sustained mental imagery and involuntary subvocalizations - Cho, Hyein; Godwin, Christine A.; Geisler, Mark W.; Morsella, Ezequiel (Frontiers in Psychology, 2014)
The conscious field includes not only representations about external stimuli (e.g., percepts), but also conscious contents associated with internal states, such as action-related intentions (e.g., urges). Although understudied, the latter may provide unique insights into the nature of consciousness. To illuminate these phenomena, in a new experimental paradigm [Reflexive Imagery Task (RIT)], participants were instructed to not subvocalize the names of visually-presented objects. Each object was presented for 10 s on a screen. Participants indicated whenever they involuntarily subvocalized the object name. Research has revealed that it is difficult to suppress such subvocalizations, which occur on over 80% of the trials. Can the effect survive if one intentionally generates a competing (internally-generated) conscious content? If so, this would suggest that intentional and unintentional contents can co-exist simultaneously in consciousness in interesting ways. To investigate this possibility, in one condition, participants were instructed to reiteratively subvocalize a speech sound (“da, da, da”) throughout the trial. This internally generated content is self-generated and intentional. Involuntary subvocalizations of object names still arose on over 80% of the trials. One could hypothesize that subvocalizations occurred because of the pauses between the intended speech sounds, but this is inconsistent with the observation that comparable results arose even when participants subvocalized a continuous, unbroken hum (“daaa….”) throughout the trial. Regarding inter-content interactions, the continuous hum and object name seem to co-exist simultaneously in consciousness. This intriguing datum requires further investigation. We discuss the implications of this new paradigm for the study of internally-generated conscious contents.